Experimental Visualization and Modeling of the Transport Behaviors of Monofilament Microplastic Fibers Through an Idealized Porous Media - Tyler T. Fouty; Nicholas B. Engdahl (Water Resources Research)
Abstract Microplastic fibers (MPF) are the largest fraction of microplastics in the environment by mass. The endpoints of these contaminants' movement is generally known at large‐scale (i.e., their origins and where they end up), but the mechanics of how they get to those sinks remains poorly understood. The objective of this work was to improve understanding of the mechanisms driving MPF migration through terrestrial systems by directly imaging their motion through idealized representations of porous media. Monofilament line with 0.3 mm diameter was passed through a bench‐scale, pseudo‐2d flow cell to capture trajectories of MPFs of three different lengths and trajectories of passive micro‐bead tracers were also captured. Video processing and automated image analysis converted the video of the experiments into a database of trajectories, allowing comparison of the experimental data to various numerical models. Simple advection‐dispersion models were adequate for modeling the passive tracer but did not provide a good description of MPF transport. A physics‐based, distributed model was able to generate realistic trajectories through the domain, but the speeds of the fibers in the initial simulation were too fast, despite working well for the passive tracer. Adding a delay (waiting time) process resulted in good description of the trajectories and travel times. The specifics of the delay process could not be deduced from these experiments, but its overall impact on transport provides mechanistic insights. These direct observation of the trajectories and speeds of MPFs moving through porous media show that MPFs likely have strong interactions with their surroundings.